MANAGEMENT IN CONDITIONS OF GLOBAL CHALLENGES AND MODERN REALITIES. METHODOLOGICAL ASPECT (Economics and region, 2024)
The development of modern economic systems is accompanied by global challenges and problems of modern realities, which have a significant impact on management and determine the need for changes in management methodology, including its key principles, changes in priorities in their selection with an orientation to adequacy, adaptability, pragmatism and professionalism. The article examines the dependence of the effectiveness of the management methodology on global challenges and dynamic problems caused by the unstable realities of today's Ukraine. A considerable number of definitions of the concept of management have been studied and analyzed, systematized and summarized, and an ontological problem has been identified for the solution of which the vision of the authors regarding the definition of the concept of management has been proposed, which outlines its essential features in a concise form. It was established that the effectiveness of the classical management methodology is limited with the growth trend by dynamic changes in circumstances and situations in the external and internal environments, the prevalence of non-linear relationships and non-functional dependencies between the factors of influence on the object of management. Economic systems function and develop in conditions of uncertainty , more situations in organizations are associated with unstructured problems that generate significant riskiness of management decisions. Significant changes to the management methodology and its modernization are proposed. In particular, such an important component as principles. In addition to the well-known classical principles, in particular, the combination of democracy and centralization, authority and responsibility, unity of leadership and collegiality, material and moral stimulation, economy and efficiency, continuity of business decisions, subordination of personal interests to the common, the authors emphasize the importance in the conditions of global challenges and modern realities principles of adequacy, adaptability, pragmatism and professionalism. The presence of many definitions of the concept of management, which on the one hand indicates the ambiguity of this concept, and on the other hand, the multiplicity of definitions of this concept leads to a significant difference in the understanding of what the object of research is, what its purpose and essential features are. To solve this ontological problem, we offer our own definition of the concept of management: management is a purposeful, complex process of managing the joint activities of people using a management methodology relevant to the requirements of specific circumstances. The purpose of this study is to improve and modernize management methodology, which, unlike natural sciences, is not characterized by determinism, accuracy and objectivity. In the course of the study, a combination of quantitative and qualitative research methods of the empirical and theoretical level of modern scientific research paradigms was used, in particular, systematization and generalization, analysis and synthesis in close combination with induction and deduction.
Keywords: management; methodology; concept; method; global challenges; process; principles; adaptability; adequacy; pragmatism